Myanmar Enterprise Survey 2014 : Early Findings - World Bank (Yangon, Myanmar, 2015)
World Bank carried out an enterprise survey in Myanmar for the first time. Enterprise survey is the world's most comprehensive company level data in emerging markets and developing economies. The enterprise survey is standardized, so it allows comparisons: (i) across countries, and (ii) across time - when the survey is repeated. Therefore, early findings are also a baseline for measuring future changes. Through analogous enterprise surveys the World Bank Group has collected data from over 130,000 firms in 130 countries, enabling regional and global comparisons. These findings will feed into the World Bank's investment climate assessment for Myanmar. The assessment will provide a comprehensive analysis of constraints for private businesses, using quantitative and qualitative data.